2020
DOI: 10.2174/1389557519666191010154444
|View full text |Cite
|
Sign up to set email alerts
|

A Series of New Hydrazone Derivatives: Synthesis, Molecular Docking and Anticholinesterase Activity Studies

Abstract: Background: Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are known to be serine hydrolase enzymes responsible for the hydrolysis of acetylcholine (ACh), which is a significant neurotransmitter for regulation of cognition in animals. Inhibition of cholinesterases is an effective method to curb Alzheimer’s disease, a progressive and fatal neurological disorder. Objective: In this study, 30 new hydrazone derivatives were synthesized. Then we evaluated their anticholinesterase activity of compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Compound 5A was docked into the active sites of AChE, BChE, COX-1, COX-2, and 5-LOX. The three-dimensional structures of all the enzymes were obtained from the Protein Data Bank with accession codes 1EVE, 4BDS, 1EQG, 1CX2, and 6N2W, respectively [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 5A was docked into the active sites of AChE, BChE, COX-1, COX-2, and 5-LOX. The three-dimensional structures of all the enzymes were obtained from the Protein Data Bank with accession codes 1EVE, 4BDS, 1EQG, 1CX2, and 6N2W, respectively [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nucleophilic substitution reaction of 3,6-dichloropyridazine with phenylpiperazine or morpholine derivatives in ethanol was carried out to produce 3-chloro-6-substituted pyridazine. The hydrolysis of 3-chloro-6-(4-(3,4-dichlorophenyl)piperazine-1-yl)pyridazine by heating in glacial acetic acid afforded 6-(4-(3-Methoxy/3-trifluoromethylphenyl)piperazi ne-1-yl/morpholino)-3(2H)-pyridazinone [19]. Subsequently, the reaction of 6-(4-(3-methoxy /3-tifluoromethylphenyl)piperazine-1-yl/morpholino)-3(2H)-pyridazinone with ethyl bromoacetate in the presence of K 2 CO 3 in acetone replaced the hydrogen atom of tertiary nitrogen atom in the pyridazinone ring and formed ethyl 6-(4-(3-methoxy/3-trifluorome thylphenyl)piperazine-1-yl/morpholino)-3(2H)-pyridazinone-2-ylacetate.…”
Section: General Chemistry Of Synthetic Schemementioning
confidence: 99%
“…Overnight in acetone (40 mL), 0.01 mol 6-(ptolyl)pyridazin-3(2H)-one (5), 0.02 mol (2.2252 mL) ethyl bromopropionate, and 0.02 mol (2.7636 g) potassium carbonate were refluxed. After cooling, the organic salts were filtered out, the solvent was removed, and the residue was refined by recrystallization with methanol to get the esters [15].…”
Section: Synthesis Of Ethyl 3-(6-oxo-3-(p-tolyl)pyridazin-1(6h)-yl)pr...mentioning
confidence: 99%
“…Pyridazinone derivatives have been suggested to offer such intriguing bioactivity as an antitumoral, antibacterialantifungal, anticonvulsant, analgesic, anti-inflammatory, antiplatelet, and anticancer impact [5][6][7][8][9][10][11][12]. Also, many of the pyridazinone derivatives have been synthesized by our research group as an inhibitor of cholinesterases which are from the serine hydrolase enzyme family [13][14][15][16][17]. It has been reported that compounds with heterocyclic ring containing nitrogen and oxygen atoms, such as oxadiazolone, benzo [1,3]oxazinon and benzoxazole, inhibit PLL.…”
Section: Introductionmentioning
confidence: 99%